Surgical Outcomes of Olecranon Osteotomy Approach Combined With Submerged Kirschner Wires and Plate Fixation for Duckerley IIIB Distal Humeral Coronal Shear Fractures - Zhou‐Feng Song; Wei‐Qiang Zhao; Zeng‐Li Zhang; Jie‐Feng Huang (Orthopaedic Surgery)
ABSTRACT Objective Duckerley type IIIB distal humerus fractures are rare and complex injuries that pose significant challenges in both diagnosis and treatment. Currently, no consensus exists on the fixation method, with existing approaches often struggling to handle small fragments and associated with issues like elbow instability. The purpose of this study is to evaluate the surgical outcomes of submerged Kirschner wires combined with plate or submerged screw fixation technique for the treatment of Duckerley type IIIB distal humerus fractures. Methods A retrospective analysis was conducted on 10 patients with Duckerley type IIIB distal humerus fractures who were treated at our hospital from February 2017 to April 2021. The treatment involved applying buried Kirschner wires combined with microplate or buried screw fixation technique through the olecranon osteotomy approach. The study included six males and four females, with a mean age of 51.4 ± 15.34 years (ranging from 22 to 69 years). During the follow‐up, the elbow range of motion, Mayo Elbow Performance Score (MEPS), American Shoulder and Elbow Surgeons (ASES) score, and complications were assessed. Results All 10 patients received regular clinical and imaging follow‐up for a mean of 39.7 ± 8.8 months (range: 25–50 months). Postoperative incision healing was good for all patients, and no neurovascular injuries were noted. Two patients developed elbow pain. At the last follow‐up before the internal fixation removal operation (9.6 ± 1.9 months), X‐ray and CT findings confirmed bony healing, and no internal fixation loosening and breakage occurred in any of the patients, except for one case in which there was displacement of the Kirschner wires. The mean range of motion of the elbow before the internal fixation removal operation was extension 15.0° ± 21.6°, flexion 129.5° ± 28.1°, pronation 83.0° ± 9.2°, and supination 81.5° ± 8.0°. The MEPS score was 83.0 ± 8.3, and the ASES was 83.6 ± 7.8. At the last follow‐up, the mean range of motion of the elbow was extension 10.0° ± 21.9°, flexion 133.5° ± 16.0°, pronation 88.0° ± 11.2°, and supination 85.0° ± 9.5°. The MEPS score was 84.6 ± 7.6, and the ASES was 84.1 ± 7.4. Conclusions The treatment of Duckerley type IIIB low distal humerus fractures using submerged Kirschner wires combined with plate or submerged screw fixation technique has satisfactory advantages in terms of fracture reduction, maintenance of the position of internal fixation, and postoperative recovery.